Organizational development of agro-industrial complex on basis of cooperation and integration - Ivanov, S.; Perebyynis, V.; Oleksenko, L.; Svitlychna, A. (Економічний вісник Донбасу, 2016)
Expediency of organizational development of the agro-industrial complex of the economy on the principles of cooperation and integration has been proved. This allows to improve organizational and economic relations between enterprises of the agriculture and food industry. Two approaches have been grounded: the first is based on the developed raw material basis; the second is limited with a lack of agricultural raw materials. The model of cooperation of agricultural enterprises and enterprises of the food industry has been formed.